Analisis Persepsi dan Harapan Masyarakat Perkotaan terhadap Kualitas Pelayanan Administrasi Kependudukan di Kota Prabumulih - Hadi, Sofwan; Hidayat, Bachtari Alam; Agus, Azwar (Nakhoda: Jurnal Ilmu Pemerintahan, 2024)
As a service provider to the public, the government must maintain the quality of its services. Quality public service is one that can meet public satisfaction. This study aims to analyze the quality of population administration services at the Department of Population and Civil Registration in Prabumulih City. The research uses a descriptive method with a quantitative approach. Data were obtained from 100 respondents through convenience/accidental sampling. Data collection was carried out by distributing a questionnaire consisting of 25 statements on a Likert scale. This study assesses the public's perception of several service dimensions, including speed, clarity of fees, the friendliness of staff, as well as the reliability and available facilities. The results show that the service is rated good, with minimal differences between public expectations and perceptions. Factors such as speed, fee clarity, and staff friendliness contribute to satisfaction. However, the physical aspects and reliability still require improvement. Recommendations include upgrading the facilities and administrative tools used in the service, as well as providing regular training for staff to support more responsive service. These improvements are expected to enhance the overall service quality and increase public satisfaction.